TANGGUNG JAWAB HUKUM PEKERJA DALAM PENGGANTIAN KERUGIAN PERUSAHAAN: STUDI KASUS PADA SEKTOR RITEL DI INDONESIA - Abdillah Abdillah; Purwanto Purwanto; Erna Susanti (Universitas Labuhanbatu, 2025)
The rapid development of the retail sector in Indonesia in the era of globalization has generated increasingly complex employment relations, including issues concerning employees’ liability for company losses. In practice, particularly within modern retail businesses such as minimarkets, wage deductions are frequently imposed on employees on the grounds of alleged negligence, cash discrepancies, inventory shortages, distribution errors, or suspected theft. This study aims to analyze the legal basis of employee liability in compensating company losses and to assess its conformity with Indonesian labor law regulations. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that employee liability must be grounded in the principle of fault-based liability and cannot be imposed unilaterally without a clear evidentiary mechanism. Wage deductions as a form of compensation for losses cannot be applied automatically, as wage policies under Law Number 13 of 2003 on Manpower (as amended) provide legal protection for employees’ wages, including limitations on fines and deductions. Therefore, a fair and proportionate legal mechanism is necessary to ensure a balanced protection between corporate interests and workers’ rights. Keywords: legal liability; employee; company losses; wage deductions; retail sector.